2014
DOI: 10.1021/la503956h
|View full text |Cite
|
Sign up to set email alerts
|

Multistep Galvanic Exchange Synthesis Yielding Fully Reduced Pt Dendrimer-Encapsulated Nanoparticles

Abstract: Here we outline a new method for synthesizing fully reduced Pt dendrimer-encapsulated nanoparticles (DENs). This is achieved by first synthesizing Cu DENs of the appropriate size through sequential dendrimer loading and reduction steps, and then galvanically exchanging the zerovalent Cu DENs for Pt. The properties of Pt DENs having an average of 55, 140, and 225 atoms prepared by direct chemical reduction and by galvanic exchange are compared. Data obtained by UV–vis spectroscopy, X-ray absorption spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
25
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 33 publications
(90 reference statements)
11
25
1
Order By: Relevance
“…Prior to immobilization atop Al 2 O 3 -modified PPF electrodes, the free G6OH(Pt 55 ) DENs were characterized using UV−vis spectroscopy and STEM ( Figures S6 and S7, respectively). The results are fully consistent with prior reports, 51,63 and they indicate the presence of Pt 55 DENs having a size of 1.3 ± 0.2 nm.…”
Section: Articlesupporting
confidence: 93%
See 1 more Smart Citation
“…Prior to immobilization atop Al 2 O 3 -modified PPF electrodes, the free G6OH(Pt 55 ) DENs were characterized using UV−vis spectroscopy and STEM ( Figures S6 and S7, respectively). The results are fully consistent with prior reports, 51,63 and they indicate the presence of Pt 55 DENs having a size of 1.3 ± 0.2 nm.…”
Section: Articlesupporting
confidence: 93%
“…We have previously shown that Pt DENs prepared by galvanic exchange are confined within their dendrimer hosts. 63,64 It is important, however, to demonstrate that they remain confined following immobilization onto the …”
Section: Journal Of the American Chemical Societymentioning
confidence: 99%
“…The magnetic UME used here consists of a Ni wire with a thin layer of Au deposited on its tip using galvanic exchange. 41 , 42 Specifically, a 50 μm Ni UME was prepared by sealing a Ni wire in a glass capillary. As shown in Scheme 2 , the Ni UME was then sealed in an acrylic plate using epoxy glue.…”
Section: Resultsmentioning
confidence: 99%
“…Although the encapsulation of MNPs inside dendrimers has been demonstrated by Crooks'groups 18 , the exact localization of MNPs in DENs still remained elusive 32 33 . Given the properties of MNPs 1 2 3 4 33 34 35 36 37 , the knowledge and understanding of this localization are important to optimize MNP engineering towards specific applications, and in particular catalysis. Here we report the relationship between the MNP localization and catalytic activity in 4-nitrophenol reduction (4-NP) to 4-aminophenol (4-AP) by NaBH 4 (refs 38 , 39 , 40 , 41 , 42 ) and CuNP-catalysed AAC reactions 43 of MNPs stabilized by either triazole-containing or triazole-free dendrimers.…”
mentioning
confidence: 99%